Beginnings of sociological family research in Serbia: From Vuk to Cvijić - Čikić Jovana M. (Baština, 2019)
Sociological and similar researches of family in Serbian society have significant tradition. Regardless of development difficulties, criticism of its theoretical (UN) foundedness, Serbian sociology of family exists as recognizable scientific discipline with noteworthy authorial opus. Considering social circumstances that shaped transformation of Serbian family life, but sociology of family as well, we can speak of four major periods in its development: pre-sociological, early-sociological, post-war/socialist and post-transition/contemporary period. We have presented standing points of four authors that marked first period - Karadžić, Bogišić, Marković and Cvijić. Based on relevant references, the aim of the paper is to point out on specific circumstances that have shaped authors' perspectives, their main findings and their significance, but also to identify major similarities and differences in their analyses of family characteristics and transformation.